2019
DOI: 10.1186/s12935-019-0747-8
|View full text |Cite
|
Sign up to set email alerts
|

A DAAM1 3′-UTR SNP mutation regulates breast cancer metastasis through affecting miR-208a-5p-DAAM1-RhoA axis

Abstract: BackgroundDishevelled-associated activator of morphogenesis 1 (DAAM1) is a member of microfilament-related formins and mediates cell motility in breast cancer (BrCa). However, the genetic mutation status of DAAM1 mRNA and its correlation with pathological characteristics are still unclearly. Methods: A patient cohort and BrCa cells were recruited to demonstrate the role of functional SNP in microRNA-208a-5p binding site of DAAM1 3′-UTR and underlying mechanism in BrCa metastasis.MethodsA patient cohort and BrC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…To further assess the association between the expression of these hub genes and the risk of breast cancer metastasis, we employed KM Plotter to evaluate the prognostic value of these genes in DMFS. The primary purpose of KM Plotter is to evaluate potential biomarkers in a meta-analysisbased manner, and many prognostic biomarkers have been identified based on this platform [51][52][53]. Five hub genes, including TPX2, KIF2C, CDCA8, BUB1B, and CCNA2, were validated to be notably associated with the shorter DMFS of breast cancer in the patient cohort based on KM Plotter.…”
Section: Discussionmentioning
confidence: 99%
“…To further assess the association between the expression of these hub genes and the risk of breast cancer metastasis, we employed KM Plotter to evaluate the prognostic value of these genes in DMFS. The primary purpose of KM Plotter is to evaluate potential biomarkers in a meta-analysisbased manner, and many prognostic biomarkers have been identified based on this platform [51][52][53]. Five hub genes, including TPX2, KIF2C, CDCA8, BUB1B, and CCNA2, were validated to be notably associated with the shorter DMFS of breast cancer in the patient cohort based on KM Plotter.…”
Section: Discussionmentioning
confidence: 99%
“… 21 SNPs in UTRs may influence the stability of mRNA, thus affecting the expression and activity of the enzyme. 42 , 43 According to a study identifying the potential SNPs related to miRNA, rs15524 may influence the hsa-miR-500a-5p that targets CYP3A5 , affecting its expression. 44 In addition, studies have found that CYP3A5*1D influences the pharmacokinetics of many drugs, including tacrolimus 45 and carbamazepine.…”
Section: Discussionmentioning
confidence: 99%
“…ab101512, Abcam) was used to visualize UBE3C expression. Previously described quantitative evaluation criteria were used [ 13 , 14 ]. Briefly, the percentage of positively stained cells was scored on a 0–4 scale: 0 (< 5%), 1 (6–25%), 2 (26–50%), 3 (51–75%) and 4 (> 75%).…”
Section: Methodsmentioning
confidence: 99%